Comparative Analysis of Anthropometric Indexs to Predict Hypertension Risk in Employees Cimahi City 2018 (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2019)
Background: Anthropometric indicator such as Body Mass Index (BMI), Waist Circumference (WC) and Waist to Height Ratio (WHtR) can to predict risk of hypertension. This study aims to compare anthropometry in predicting risk of hypertension in employees Cimahi City by gender. Methods: Design study was Cross Sectional with Diagnostic Test. This study used secondary data Non Communicable Diseases (NCD) screening in 827 employees with age ≥ 15 years. The ROC (receiver operating characteristic) curves were analyzed to identify the optimal cut off points and compare the predictive capacity of the anthropometric indicators for the hypertension outcome by gender using Stata.13 software. Result: The hypertension in men 65.32% more than women 34.68%. The Area Under the Curve (AUC) of WC 0.70 (95%CI=0.66-0.74) more than WHtR 0.66 (95%CI=0.62-0.70) and BMI 0.64 (95%CI=0.60-0.69). Based on gender,in men the highest AUC WC 0.69 (95%CI=0.64-0.75) while in women the highest AUC were in WC and WHtR was 0.67 (95%CI=0.60-0.74). The optimal cut off point in predicting hypertension were BMI 25.89 (Sn=67.05%,Sp=57.95%),WC 90 cm (Sn=76.30%,Sp=54.74%) and WHtR 0,56 (Sn=68.79%,Sp=59.02%). Conclusion: The WC is the most superior anthropometric index compared to the WHtR and BMI in predicting hypertension risk in employees in Cimahi City.